Hearing loss in Muckle‐Wells syndrome. Issue 3 (25th February 2013) - Kuemmerle‐Deschner, Jasmin B.; Koitschev, Assen; Ummenhofer, Katharina; Hansmann, Sandra; Plontke, Stefan K.; Koitschev, Christiane; Koetter, Ina; Angermair, Eva; Benseler, Susanne M.
Abstract Objective Muckle‐Wells syndrome (MWS) is an inherited autoinflammatory disease characterized by fevers, rashes, arthralgia, conjunctivitis, and sensorineural hearing loss. In MWS, NLRP3 gene mutations are associated with excessive interleukin‐1 release. The aims of this study were to determine the otologic characteristics of MWS, define trajectories of hearing loss, and explore the association with distinct NLRP3 genotypes. Methods A prospective observational cohort study of children and adults diagnosed as having MWS was conducted at a single center. NLRP3 gene mutations were determined. Patients underwent standardized clinical, laboratory, and otologic assessments, including pure tone audiometry, vestibular organ testing, and tinnitus evaluation. Trajectories of hearing loss were defined for each genotype. The genotype‐specific risk of progression of hearing loss was determined. Results A total of 33 patients ages 3–75 years who were members of 5 families with 4 different NLRP3 gene mutations were included. The majority of patients (67%) experienced bilateral sensorineural hearing loss. Even in cases of profound hearing loss vestibular reactivity remained normal. Fourteen adult patients reported nondebilitating tinnitus. Overall, hearing impairment progressed with age. Patients with the T348M mutation were at highest risk of rapid progression of sensorineural hearing loss. Conclusion Patients with MWS are at risk of developing progressive sensorineural hearing loss without vestibular involvement. Hearing impairment starts at high frequencies and can subsequently progress to profound hearing loss. Progression is age dependent. Patients with different NLRP3 mutations had distinctly different trajectories of hearing loss, suggesting a mutation‐specific risk that should be considered when making treatment decisions.